An evaluation of the management of customer experiences by Zimbabwean commercial banks. - Muvezwa, Joyline R. (Midlands State University, 2017)
The research investigates the management of customer experience by Zimbabwean commercial banks. The Zimbabwean banking sector has witnessed significant changes characterized by rebranding of some banks, increased stiff competition, and the uneven shaky playing field/unstable environment. Most of the products being offered by the banks have become standardised therefore banks are being forced to orient their strategies towards customers instead of products making customer experiences a very key factor in strategic management. This research aimed at exploring the customer experience management practices through an analysis of existing literature as well as a survey which was conducted amongst commercial banks in Zimbabwe. The research used the descriptive survey research design and the study population elements comprised of people from the marketing departments, human resources department, the retail banking division and bank customers. Non random sampling was used to select participants and the sample size was derived from the study population. Research instruments used were questionnaires and interviews. Data analysis was done using SPSS computer package and moderate statistical principles such as frequencies and percentages were used to analyze the data. Presentation of findings was done by way of graphs, tables and verbatim. The study revealed that banks were doing very little to align their services to meet customer expectations. The study held that employees in the Zimbabwean banking sector were not adequately motivated to have customer centric values. The study also showed that the physical evidence was attractive and convenient and contributed positively towards their perceptions about their banks. The researcher recommended that Zimbabwean Commercial banks involve their customers during product development. If possible, the physical evidence should not be standard but should be tailor made to suit customer needs. The researcher recommended that Customer experience management strategies should be clearly defined in the form of a service blueprint further study on customer experience strategies implementation and its impact on customer loyalty should also be carried out.